Pembrolizumab in men with heavily treated metastatic castrate‐resistant prostate cancer. (3rd July 2019) - Tucker, Matthew D.; Zhu, Jason; Marin, Daniele; Gupta, Rajan T.; Gupta, Santosh; Berry, William R.; Ramalingam, Sundhar; Zhang, Tian; Harrison, Michael; Wu, Yuan; Healy, Patrick; Lisi, Stacey; et al.
Abstract: Background: Pembrolizumab is approved for patients with metastatic, microsatellite instability (MSI)‐high or mismatch repair‐deficient (dMMR) solid tumors. However, very few men with prostate cancer were included in these initial studies. Methods: We performed a single institution retrospective review of men with metastatic castrate‐resistant prostate cancer (mCRPC) who were treated with pembrolizumab. The primary objective was to describe the clinical efficacy of pembrolizumab associated with patient and genomic characteristics. Results: We identified 48 men who received ≥1 cycle of pembrolizumab for mCRPC. Of these, 94% (45/48) had ≥3 prior lines of therapy for mCRPC. Somatic tumor sequencing was available in 18/48 men (38%). We found that 17% (8/48) had a ≥50% confirmed PSA decline with pembrolizumab, and 8% (4/48) had a ≥90% PSA decline with durations of response ranging from 3.1 to 16.3 months. Two of these four men had mutations in LRP1b, one of whom also had MSH2 loss and was MSI‐H and TMB‐high. Despite prior progression on enzalutamide, 48% (23/48) of men were treated with concurrent enzalutamide. The median PSA progression‐free‐survival was 1.8 months (range 0.4‐13.7 months), with 31% of patients remaining on pembrolizumab therapy and 54% of men remain alive with a median follow‐up of 7.1 months. Conclusions: In a heavily pretreated population of men with mCRPC, pembrolizumab was associated with a ≥50% PSA decline in 17% (8/48) of men, including a dramatic ≥90% PSA response in 8% (4/48), two of whom harbored pathogenic LRP1b mutations suggesting that LRP1b mutations may enrich for PD‐1 inhibitor responsiveness in prostate cancer. Abstract : A subset of men with heavily treated metastatic castrate resistant prostate cancer derives clinical benefit from treatment with pembrolizumab. Tumor biomarkers such as microsatellite instability are being used to help identify some of these men; more investigation into potential biomarkers such as LRP1b are needed to help identify others who may derive benefit.